Constructing Illegitimacy? Cartels and Cartel Agreements in Finnish Business Media from Critical Discursive Perspective - Siltaoja, Marjo E. (Journal of business ethics, 2010)
During the last decade, any questionable or illegal behaviour on the part of businesses has received considerable attention in the media. Using a critical discursive perspective, we here investigate how the media constructs one type of questionable business as illegitimate. Our data draw upon articles dealing with cartels and cartel agreements in Finnish business media covering the five year period 2002–2007. Our contributions are following: We add to the current literature on CSR and national businesses, suggesting that regardless of globalization socio-cultural history plays an important role in constructing the illegitimacy of business practices. We therefore emphasize the importance of media as an arena where social actors construct the social contract between business and society. We further contribute to studies on questionable business by reconstructing a discursive framework used to construct cartels and cartel agreements.